The Complete Amino Acid Sequence for the Anaerobically Induced Aldolase from Maize Derived from cDNA Clones - Kelley, Philip M. (1986)
A cDNA library was synthesized from maize anaerobic root mRNA and screened with cDNA specific to the anaerobically induced Zea mays cytoplasmic aldolase. At least 1% of the cDNA of the library corresponded to maize cytoplasmic aldolase. The sequence of four overlapping cDNA clones encoded a protein of molecular weight 38,611 homologous to aldolase. These cDNAs were polymorphic at three bases and one of these cDNAs had a different, shorter 3′-untranslated region. No known eukaryotic poly(A) addition site was detected. The derived amino acid sequences of maize was compared to the sequence of aldolase of trypanosome, Drosophila, and two mammalian isozymes, A and B. Of these, maize cytoplasmic aldolase was found to have the highest homology (55%) with rabbit aldolase A.